Design of a multi‐mode digital pixel with conversion data protection - Yan‐Hua Ma; Xiang‐He Kong; Yu‐Chun Chang (IET Circuits, Devices and Systems)
Abstract With the development of semiconductor technology, digital pixel has received widespread attention and is applied to various electronic products. However, due to the limitation of area, it forms a challenging task to design a digital pixel with multiple modes. In this paper, a pulse width modulation based digital pixel is proposed, which is compatible with five different modes. By using the multi‐purpose capacitors and static random access memory structure, it can realise multi‐mode conversion in an equivalent area to that of the single mode digital pixel without performance degradation. Furthermore, a corresponding logic control method is developed, such that the integrity of the frame data is ensured during mode conversion. The simulation result of our proposed digital pixel in Tower Jazz 0.18 μm process shows that in the bright field it achieves a dynamic range of 67 dB. In the dark field, it achieves a conversion gain up to 13.91 μV/e−, with input noise of 37.89 e−per pixel after correlated double sampling.